Amino acid sequence of bovine spleen cathepsin B - Meloun, B; Baudys, M; Pohl, J; Pavlík, M; Kostka, V (The Journal of biological chemistry, 1988)
The complete amino acid sequence of bovine spleen cathepsin B was determined by manual and automatic Edman degradation of fragments prepared by proteolytic or chemical digestion of the enzyme. The single-chain form of the enzyme consists of 253 amino acid residues and its Mr is 27,468 (carbohydrate moiety not included). The light chain (residues 1-47) and the heavy chain (residues 50-253) of the enzyme are linked by the sequence -Gly-Arg (residues 48 and 49) in the single-chain form. Bovine spleen cathepsin B shows 80% sequence homology with cathepsins B from other species. An outstanding feature of bovine spleen cathepsin B not observed with the other cathepsins B is the presence of two additional half-cystine residues.
Keywords: kathepsin B; Humans; druhová specificita; Molecular Sequence Data; molekulová hmotnost; sekvenční homologie nukleových kyselin; molekulární sekvence - údaje; krysa rodu Rattus; lidé; zvířata; Amino Acid Sequence; Cattle; Spleen; Sequence Homology, Nucleic Acid; skot; Species Specificity; Cathepsin B; Rats; Animals; slezina; sekvence aminokyselin; Molecular Weight